Economic Analysis of Occupational Risk Prevention in the Construction Sector - Ramos, Delfina G. (2013)
The construction sector has one of the worst occupational safety and health records in Europe. The costs of this scenario are very high, namely costs for workers and their families, costs to organizations, resulting from the absence of workers due to illness, insurance premiums, costs resulting from reduced productivity, cost of replacement and training of workers, etc., and costs to society, which in turn increases the costs of health systems. This paper presents and discusses the development of a methodology for economic evaluation in the context of risk management, which will allow senior management to support decision making. The possible application of this methodology to the construction sector is discussed.